Regular Quality Management Audit in Nuclear Medicine Services - A Dynamic Approach of Self Improvement (Bangladesh Journal of Nuclear Medicine, 2018)
Abstract not availableBangladesh J. Nuclear Med. 19(1): 51-55, January 2016